2017 IEEE Conference on Antenna Measurements &Amp; Applications (CAMA) 2017
DOI: 10.1109/cama.2017.8273435
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the fat tissue channel for intra-body microwave communication

Abstract: Recently, the human fat tissue has been proposed as a microwave channel for intra-body sensor applications. In this work, we assess how disturbances can prevent reliable microwave propagation through the fat channel. Perturbants of different sizes are considered. The simulation and experimental results show that efficient communication through the fat channel is possible even in the presence of perturbants such as embedded muscle layers and blood vessels. We show that the communication channel is not affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Fat tissue appears to be the easiest tissue for the propagation in terms of propagation velocity and losses [5,6,10,[19][20][21]. Fat as a propagation channel has been a topic for few recent papers [19][20][21], which have verified by simulation and measurement based studies that the fat tissue is promising propagation medium is the ultra wideband (UWB) based medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Fat tissue appears to be the easiest tissue for the propagation in terms of propagation velocity and losses [5,6,10,[19][20][21]. Fat as a propagation channel has been a topic for few recent papers [19][20][21], which have verified by simulation and measurement based studies that the fat tissue is promising propagation medium is the ultra wideband (UWB) based medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fat-IBC technique reliability has only been looked into by several works in the context of parameters capable of influencing the channel's performance. Examples of recent investigations include those that affect the transmission channel, such as embedded muscle tissue [28], nonhomogeneous fat tissue thickness [27], and blood vessel [29]. The outcomes of these experiments revealed fat-IBC's capacity for excellent communication even in the presence of up to 60 % obstacles of channel height [28].…”
Section: Intra-body Communication (Ibc) Can Be Described As a Communimentioning
confidence: 99%
“…Examples of recent investigations include those that affect the transmission channel, such as embedded muscle tissue [28], nonhomogeneous fat tissue thickness [27], and blood vessel [29]. The outcomes of these experiments revealed fat-IBC's capacity for excellent communication even in the presence of up to 60 % obstacles of channel height [28]. The signal transmission was not impacted by obstacle less than 15 mm cube and it starts to degrade when the 25 mm height channel is perturbated with a perturbating tissue of size 15 mm cube and above.…”
Section: Intra-body Communication (Ibc) Can Be Described As a Communimentioning
confidence: 99%
“…Asan et al [ 20 ] have successfully shown approximately 96% data packet reception through the fat tissue for a fat channel of length 10 cm. It has been shown that the communication through the fat tissue is still possible even at 60% obstruction due to embedded muscle tissues [ 21 ]. To design stable and reliable fat iBAN links, it is important to assess the microwave propagation losses along the fat channel.…”
Section: Introductionmentioning
confidence: 99%